Analysis of The Determination of Rail-Based Urban Transportation Routes in The City Of Manado (Case Study: Zero Point Manado - Sam Ratulangi International Airport) - Shofian Edy Harianto Bongso; Lucia Ingrid Regina Lefrandt; Oktovian Berty Alexander Sompie (Eduvest - Journal of Universal Studies, 2025)
Consequently, the activities that develop as a result of the formation of activity/land use centers such as government administration centers, residential areas, schools, hospitals, entertainment facilities, shopping centers, tourism accommodation centers, causes huge movement generation which affects the existing transportation systems. It can be concluded that the resulting travel time will decrease with a large enough passenger carrying capacity. The recommended form is the type of LRT (Light Rail Transit) with rail-based technology. The method used in this research is literature study, primary data collection in the form of household interview surveys, and secondary data collected from several related institutions. The survey results were analyzed with the help of Microsoft Office Excel and modeling using a linear regression equation with the independent variables measured, namely family composition (X1), number of working members (X2), number of members attending school (X3), number of members working and attending school (X4), vehicle ownership (X5), family income (X6), and the dependent variable (Y) as the number of family movements per day. The modeling results obtained the best equation, namely Y=1.394+0.888X1 and the Determinant Coefficient (R²) value obtained was 0.824 or 82.4%. LRT (Light Rail Transit) line concept with the starting point of the Station Zero Point Manado - Paal Dua Station 1 - Paal Dua Station 2 - Manado-Bitung Toll Gate Station - Manado-North Minahasa Station - Mapanget Station - Sam Ratulangi International Airport Station with a total of 7 stations and 6 segments and a total length of 15,400 meters.